1998
DOI: 10.1097/00000539-199807000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Patient-Controlled Analgesia with Morphine, Continuous Epidural Analgesia, and Continuous Three-in-One Block on Postoperative Pain and Knee Rehabilitation After Unilateral Total Knee Arthroplasty

Abstract: In this study, we determined that, after total knee arthroplasty, loco-regional analgesic techniques (epidural analgesia or continuous 3-in-1 block) provide better pain relief and faster postoperative knee rehabilitation than i.v. patient-controlled analgesia with morphine. Because it causes fewer side effects than epidural analgesia, continuous 3-in-1 block is the technique of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
302
2
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(322 citation statements)
references
References 17 publications
8
302
2
6
Order By: Relevance
“…Two prospective randomized studies examined 3 different modes of analgesia: continuous femoral nerve block, epidural analgesia, and intravenous narcotic therapy after TKA. 47,48 These studies showed improvement in perioperative rehabilitation scores and a decreased duration of stay in a rehabilitation center for patients receiving the regional anesthesia techniques. Continuous femoral nerve block was shown to have equivalent analgesia with fewer side effects than epidural analgesia in both of these studies.…”
Section: Approaches To the Lower Extremitymentioning
confidence: 96%
See 2 more Smart Citations
“…Two prospective randomized studies examined 3 different modes of analgesia: continuous femoral nerve block, epidural analgesia, and intravenous narcotic therapy after TKA. 47,48 These studies showed improvement in perioperative rehabilitation scores and a decreased duration of stay in a rehabilitation center for patients receiving the regional anesthesia techniques. Continuous femoral nerve block was shown to have equivalent analgesia with fewer side effects than epidural analgesia in both of these studies.…”
Section: Approaches To the Lower Extremitymentioning
confidence: 96%
“…Continuous femoral nerve block has been shown to improve outcome after major knee and vascular surgery of the lower extremity compared with intravenous narcotic therapy or continuous infusion or injection of analgesics. [44][45][46][47][48][49][50] Chelly et al 46 showed a 20% reduction in hospital length of stay in patients receiving continuous femoral nerve block analgesia compared with patients receiving intravenous patient-controlled analgesia narcotics after major knee surgery. Two prospective randomized studies examined 3 different modes of analgesia: continuous femoral nerve block, epidural analgesia, and intravenous narcotic therapy after TKA.…”
Section: Approaches To the Lower Extremitymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Continuous peripheral nerve blocks provide superior analgesia compared with intravenous patient-controlled analgesia and a lower incidence of side effects compared with either intravenous patient-controlled analgesia or continuous lumbar epidural analgesia. [2][3][4][5] Prospective, randomized clinical studies have demonstrated the effectiveness of ambulatory continuous peripheral blocks after painful orthopedic procedures. 6,7 A major concern with the use of continuous peripheral nerve block is placement of the catheter close enough to the nerve to allow effective analgesia with the small amounts of dilute local anesthetic solutions utilized for the "secondary analgesic block" after the initial primary anesthetic block has resolved.…”
mentioning
confidence: 99%
“…160,161 Most studies comparing this method directly to intravenous patient-controlled analgesia (PCA) have demonstrated superior pain relief at rest and with movement, better postoperative knee flexion, and earlier discharge. 162,163 Unfortunately, the increased cost of this technique and lack of expertise in placing peripheral nerve catheters often limits their use. Whenever peripheral nerve techniques (either single shots or catheters) are used, it is very important that anaesthesiologists and physiotherapists engage in dialogue in order to reach rehabilitation goals and avoid the delay in functional recovery that can be caused by dense motor blockade.…”
Section: Continuous Peripheral Nerve Cathetersmentioning
confidence: 99%